Validity of auditory perceptual assessment of velopharyngeal function and dysfunction – the VPC-Sum and the VPC-Rate. (2nd September 2017) - Lohmander, Anette; Hagberg, Emilie; Persson, Christina; Willadsen, Elisabeth; Lundeborg, Inger; Davies, Julie; Havstam, Christina; Boers, Maria; Kisling-Møller, Mia; Alaluusua, Suvi; Aukner, Ragnhild; Pedersen, Nina Helen; et al.
ABSTRACT: Overall weighted or composite variables for perceptual auditory estimation of velopharyngeal closure or competence have been used in several studies for evaluation of velopharyngeal function during speech. The aim of the present study was to investigate the validity of a composite score (VPC-Sum) and of auditory perceptual ratings of velopharyngeal competence (VPC-Rate). Available VPC-Sum scores and judgments of associated variables (hypernasality, audible nasal air leakage, weak pressure consonants, and non-oral articulation) from 391 5-year olds with repaired cleft palate (the Scandcleft project) were used to investigate content validity, and 339 of these were compared with an overall judgment of velopharyngeal competence (VPC-Rate) on the same patients by the same listeners. Significant positive correlations were found between the VPC-Sum and each of the associated variables (Cronbachs alpha 0.55–0.87, P < 0.001), and a moderately significant positive correlation between VPC-Sum and VPC-Rate (Rho 0.698, P < 0.01). The latter classified cases well when VPC-Sum was dichotomized with 67% predicted velopharyngeal competence and 90% velopharyngeal incompetence. The validity of the VPC-Sum was good and the VPC-Rate a good predictor, suggesting possible use of both measures depending on the objective.